LGBT DI INDONESIA : Perspektif Hukum Islam, HAM, Psikologi dan Pendekatan Maṣlaḥah - Rustam DKA Harahap (Faculty of Sharia and Law, Universitas Islam Negeri (UIN) Walisongo Semarang, 2016)
This study aims to discuss LGBT phenomenon in Indonesia in Islamic law, human rights (HAM), and psychological prespectives. In general, this controversy can be classified into three perspectives, First, religious classification that represented by religious prominent figures and religious organizations particularly Islam, the second, both activists and human rights activists, and the third, psychologist profession. According to the psychological perspective, LGBT is a disease that has a possibility to be cured. According to Islamic law and human rights, LBGT groups must be protected in the form of health insurance by helping and treating them from the disease to be normal. But, the LGBT community activities that contradict with religious norms and interfere the other human rights, then according to the Islamic law and human rights perspectives, such activities should be banned, even they can be subjected to sanctions.